A Synthesis of Research Regarding the Validity of the Theory of Multiple Intelligences as an Approach to General Education and TESOL - Gardiner, Brian (2016)
Gardner’s 1983 ‘Theory of Multiple Intelligences’ has inspired educators the world over for over three decades. Due to the fact that this approach to education implies the use of alternative assessment methods and that most of the research studies on Multiple Intelligences contain a large amount of qualitative reports from various stakeholders at these schools, the present study sought to quantify positive learning outcomes expressed as ‘Feuerstein’s socialconstructivist, language-learning, mediation variables,’ and a selection of variables related to ‘tenets of the Multiple Intelligences approach to education,’ with the goal of accounting for as much of the variance in assessment performance on either internally- or externally- monitored standardized exams as possible. Hinging on a statistical analysis using Spearman principle factor analysis, two themes emerged from the data of 20 peer- or externally-reviewed studies on the outcomes of approaching both general and ESOL education through Multiple Intelligences Theory. These themes, ‘progressing from amateur to expert learner’ and ‘cooperation with others’ were then shown to associate with the ESOL vocabulary learning-strategies model of Tseng, Dörnyei, and Schmitt (2006), and contextualized through a discussion of refugee English as a Second Language (ESL) programs in the U.S.A. and the U.K., which could stand to benefit from a cooperative, Multiple Intelligences, learning community, where individual differences are respected, self-regulation in the learning process is encouraged, and job-training is integrated with language learning.